2016
DOI: 10.1007/s11356-016-6724-z
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol emissions of a ship diesel engine operated with diesel fuel or heavy fuel oil

Abstract: Gaseous and particulate emissions from a ship diesel research engine were elaborately analysed by a large assembly of measurement techniques. Applied methods comprised of offline and online approaches, yielding averaged chemical and physical data as well as time-resolved trends of combustion by-products. The engine was driven by two different fuels, a commonly used heavy fuel oil (HFO) and a standardised diesel fuel (DF). It was operated in a standardised cycle with a duration of 2 h. Chemical characterisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 70 publications
5
85
0
Order By: Relevance
“…Overall, light absorption by OM in DF and MGO exhaust was found to be negligible, whereas absorption by OM in HFO PM was very significant. This result was not surprising considering the near black color of the HFO fuel (diesel is almost transparent) and the molecular similarity between HFO‐exhaust OM and the fuel (Sippula et al, ; Streibel et al, ). In more detail, our conclusions are as follows.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Overall, light absorption by OM in DF and MGO exhaust was found to be negligible, whereas absorption by OM in HFO PM was very significant. This result was not surprising considering the near black color of the HFO fuel (diesel is almost transparent) and the molecular similarity between HFO‐exhaust OM and the fuel (Sippula et al, ; Streibel et al, ). In more detail, our conclusions are as follows.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, differences in fuel composition may influence marine engine PM optical properties. Since the molecular composition of HFO PM has been shown to be comparable with the molecular composition of HFO (Streibel et al, 2017), in a manner depending on engine load (Sippula et al, 2014), we hypothesize that the molecular composition of brC is also related to the molecular composition of the fuel. In support of this hypothesis, we note that Sippula et al (2014) observed larger mass fractions of PAHs in HFO OM at lower engine loads, similar to our observation of increased MAC OM at lower engine loads.…”
Section: Expected Differences Between Engines and Hfo Samplesmentioning
confidence: 93%
See 1 more Smart Citation
“…5a, and because multiple soluble molecules found in HFO fuel have also been detected in HFO-PM. 36,46 To test this hypothesis, we performed stepwise solvent extraction of four HFO-PM filter samples, measuring the sample absorption after each step. The results for a representative filter are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent comparative study focused on HFO and MDO in the European sulfur emission control area (SECA) showed that a decline in sulfur content from 0.48 to 0.092 % led to a reduction of 67 % in PM mass and 80 % in SO 2 emissions (Zetterdahl et al, 2016). Another comprehensive study including PM, EC and heavy metals was undertaken to compare HFO and standardized diesel fuel (Streibel et al, 2017). Following the regulations for using low sulfur fuels implemented by western countries, China began to launch its own stepwise regulations associated with domestic emission control areas (DECAs) to minimize conventional pollutants from shipping emissions.…”
Section: Introductionmentioning
confidence: 99%